Nursing Care For Patients With Ischemic Heart Disease (The Review of Diabetic Studies, 2024)
Nursing care for patients with ischemic heart disease (IHD) constitutes a comprehensive, evidence-based, and patient-centered practice that is critical to optimizing outcomes across the entire disease spectrum, from primary prevention and acute intervention to long-term rehabilitation and secondary prevention. Grounded in a thorough understanding of coronary pathophysiology, nursing interventions are dynamically tailored to the individual’s phase of illness, beginning with rapid assessment, symptom management, and facilitation of timely reperfusion during acute coronary syndromes to minimize myocardial damage. Beyond the acute setting, nurses assume a pivotal educational and supportive role, empowering patients through meticulous instruction on medication adherence, risk factor modification, and symptom recognition, which are fundamental to preventing disease progression and recurrent events. Furthermore, by providing holistic psychosocial support, coordinating care transitions, and advocating for participation in structured cardiac rehabilitation, nurses address the multifaceted biopsychosocial needs of patients, thereby enhancing quality of life, promoting self-efficacy, and improving long-term survival within the framework of guideline-directed medical therapy.